Synthesis and Characterisation of Magnetic Nanoparticles for Lung Cancer Detection and Therapy - T., Manikandan; V. , Nandalal; S. , Joshua Kumaresan; J.L. , Mazher Iqbal; A. , Muruganandham (International Journal of Psychosocial Rehabilitation, 2020)
The main cause for cancerous deaths in men is lung cancer. It has been reported that smoking cigarettes/beedis is the major reason for lung cancer deaths (90%) in the world. The lung cancer also develops in non-smokers (people who do not smoke), but the chance is ten times less than in people who smoke. Detecting lung cancer in its initial stages is quite difficult. Treating the lung cancer in its advanced stages involves surgical removal of the cancer-affected portion of the lung, chemotherapy, and radiation therapy. To detect the cancer in its early stage, nanotechnology is used. This paper focuses on the lung cancer detection by reaction of polymer-coated magnetic nanoparticles with the cell line samples. The experimental results show that the polymer-coated magnetic nanoparticle can detect and treat the lung cancer.